Pembelajaran kosakata Bahasa Mandarin siswa kelas X lintas minat 1 SMA Negeri 1 Batu dengan pemanfaatan media 幸运轮子 [Xìngyùn Lúnzi] - Setyorini, Asri (2020)
This study is aimed to describe the process of implementation 幸运轮子 [xìngyùn lúnzi] media in learning vocabulary for the tenth graders students of Mandarin cross major 1 of State Senior High School 1 Batu and to find out students' and Mandarin teachers' responses about this media. The material used in this study was basic competence 3.4 about school' equipment, animal and public building. Data analysis was adopted from Miles dan Huberman model. These steps were classified into four parts; data collection, data reduction, data display and conclusion.